Acute Bilateral Foot Drop as Presenting Symptom of Hemorrhagic Synovial Cyst of Lumbar Spine - (:unkn) unknown (ELSEVIER SCIENCE INC, 2017)
BACKGROUND: Acute bilateral foot drop is a rare clinical presentation. CASE DESCRIPTION: A 77-year-old male presented with acute bilateral weakness of the foot and ankle dorsiflexion. Magnetic resonance imaging of the lumbar spine revealed ligamentum flavum hypertrophy, as well as a mass lesion that appeared hyperintense on T1-weighted images and hypointense on T2-weighted images. Emergent decompressive laminectomy and hemorrhagic synovial cyst excision were performed. Histopathologic examination of the tissue revealed a synovial cyst with hemorrhage. CONCLUSION: Here, we describe a unique case of a hemorrhagic synovial cyst with a presenting symptom of acute bilateral foot drop.
Keywords: Bilateral foot drop; Hemorrhagic lumbar synovial cyst; Surgery; PATHOGENESIS; DIAGNOSIS